Emotional Intelligence and Its Relationship with Service Quality: Case Study from the Palestinian Central Bureau of Statistics - Al-Qubbaj, Ihab Sameer; Malak, Falastin Ramadan (Jordan Journal of Business Administration, 2022)
This study aims to identify the emotional intelligence dimensions (skills) of the employees of the Palestinian Central Bureau of Statistics (PCBS) and their relationship to the quality of the actual services provided by the PCBS. To achieve the objectives of this study, the researchers used the analytical descriptive approach and the correlational approach. The population of this study represents all the employees in the (PCBS) holding supervising degrees and occupying the positions of (head of a division, assistant manager, manager and general manager), who are (165) in number. A random sample consisting of (100) individuals was chosen from the study population. A questionnaire was distributed directly to them and a total of (90) questionnaire forms were returned, of which (84) were valid for analysis, with a percentage of approximately (51%), which is a suitable percentage for scientific research purposes. To get the results of the study, the statistical analysis program (SPSS) was used to analyze the collected data. The results illustrated that the emotional intelligence dimensions (skills) of the employees of PCBS were at the middle level and above. Moreover, the results indicated that the quality of the actual services provided by the (PCBS) is of a high level. The study concluded that all dimensions (skills) of emotional intelligence have a high predictive ability of the quality of the actual services provided by the (PCBS) organization, but in various degrees. According to the results, the most influential emotional intelligence dimension on the actual quality of service was the social skills dimension, followed by the motivation skills dimension. However, the least influential one was the empathy skills dimension. Regarding the level of the provided service quality, it was found to be high with the reliability dimension in the first rank and the empathy dimension in the last rank. The study presented many recommendations, the most important of which is that the emotional intelligence skills of (PCBS) employees should be enhanced by giving them the necessary training, in addition to that the PCBS should educate its employees about the concept of emotional intelligence.